I can learn: spelling - Apsely, Brenda (Egmont London, 2005)
"I Can Series" is a collection of children's books that focus on empowering young readers by promoting self-confidence and resilience. Each book centers on a character who overcomes challenges and learns important life lessons, encouraging kids to believe in themselves and their abilities. The stories often include relatable scenarios, inspiring messages, and vibrant illustrations, making them engaging and uplifting for young audiences.